(untitled) (El Hilo de la Fabula, 2023)
The current moment could only be compared to a crime movie, but this time we are the criminals, the humans. The author wonders what kind of planet we will leave as a legacy to our children. Humans should be less self-centered and indifferent and more aware of the ethical and ecological problems of the planet. A collective perspective would be necessary, regardless of the different cultures.